Darwin wasps of the subfamily Pimplinae (Hymenoptera: Ichneumonidae) of Mexico: Ephialtes genus-group - Khalaim, Andrey I.; Ruíz-Cancino, Enrique (Zootaxa, 2022)
Mexican species of nine genera of the Ephialtes genus-group (Ichneumonidae: Pimplinae) have been reviewed: Acropimpla Townes (1 species), Anastelgis Townes (3 species), Calliephialtes Ashmead (6 species, including one unidentified taxon), Dolichomitus Smith (4 species), Endromopoda Hellén (1 species), Ephialtes Grav. (1 species), Iseropus Förster (1 species), Liotryphon Ashmead (4 species) and Scambus Hartig (16 species, including six morphospecies). Seven species are described as new to science: Acropimpla tequila Khalaim & Ruíz-Cancino, sp. nov., Anastelgis chiapasana Khalaim & Ruíz-Cancino, sp. nov., Endromopoda daschi Khalaim, sp. nov., Liotryphon gauldi Khalaim, sp. nov., L. tamajalus Khalaim & Ruíz-Cancino, sp. nov., Scambus irapuatoensis Khalaim & Ruíz-Cancino, sp. nov. and S. longicoxa Khalaim, sp. nov. Scambus basseyi Gauld, 1991 is found to be a junior synonym of S. crassicauda (Cresson, 1874) (syn. nov.). Two genera, Acropimpla and Endromopoda, and species Anastelgis garciai Gauld, Calliephialtes notanda (Cresson), Scambus aplopappi (Ashmead) and S. emeritae Gauld are recorded for the first time from Mexico; Anastelgis garciai Gauld is also newly recorded from Panama, Dolichomitus irritator (F.) from Honduras, Scambus albipes (Cresson) from Guatemala and S. arizonensis Walley from Guatemala and Honduras. Identification keys to the species occurring in Mexico are provided.